Penerapan Metode At-Tartil Pada Pembelajaran Al-Qur’an Di TPQ Nurul Qur’an Banjaran Driyorejo Gresik - Ahmad Yusril Amin; Mulyadi; Barudin (Jurnal Pendidikan Agama Islam Miazhar, 2022)
In fact, the Al-Qur'an is a holy book as well as the main source and lessons of the Islamic religion, which is a guide for human life, as an incomparable blessing for the universe, in the Al-Qur'an it also regulates relationships with each other (Hablu min Allah waHablumin al- Nas) as well as humans and their environment. Based on the problems above, the problem in this research is: How to Apply the At-Tartil Method to Learning the Qur'an at TPQ Nurul Qur'an Banjaran Driyorejo Gresik. The results of this study indicate that in practice the application of the At-Tartil method to learning the Qur'an at TPQ Nurul Qur'an Banjaran has been going well and effectively in accordance with the guidelines and rules set by the central institution BMQ At-Tartil Sidoarjo Center, by applying the At-Tartil method through Talqin and Ittiba' which is then followed by the classic urdloh in each class with an allotted time of 90 minutes. And to find out the level of success of each student, daily evaluations and level evaluations (volume increases) are carried out by each class teacher and also a final evaluation carried out by the munaqsyp team at BMQ At-Tartil Sidoarjo when students complete all the material in the At method book -Tartil, so that the queue is accustomed to reading the Qur'an using the At-Tartil method and students are sensitive to wrong readings of the Qur'an, sensitive in the sense of knowing and having the awareness to justify the reading. The application of the At-Tartil method cannot be separated from several supporting factors, namely teachers who are professional in their field (the At-Tartil method), the creation of effective and efficient learning that is also conducive, the availability of adequate facilities and infrastructure, the amount of community support, a strategic location, and there are no burdensome costs for guardians. While the inhibiting factors are differences in the level of understanding between students in one class, lack of cooperation between teachers and guardians, lack of awareness of the students' guardians of the importance of learning the Qur'an and also an increasingly sophisticated environment with the times.